Pengaruh Return on Assets (ROA), Debt To Equity Ratio (DER), dan Current Ratio (CR) Terhadap Harga Saham Perusahaan Rokok di Bursa Efek Indonesia Periode 2017-2024 - Beni Seftiawan; Poppy Indriani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the effect of Return on Assets (ROA), Debt to Equity Ratio (DER), and Current Ratio (CR) on the stock prices of cigarette companies listed on the Indonesia Stock Exchange (IDX) during the 2017–2024 period. The data used are secondary data obtained from annual financial reports and stock prices of four cigarette issuers: PT Gudang Garam Tbk, PT Hanjaya Mandala Sampoerna Tbk, PT Bentoel Internasional Investama Tbk, and PT Indonesian Tobacco Tbk. The analysis method used is multiple linear regression with classical assumption tests. The results show that partially, ROA and CR have a significant positive effect on stock prices, while DER has a significant negative effect. Simultaneously, the three variables significantly affect stock prices. These findings support the signaling theory and provide important implications for investors and company management in making financial decisions.